Endorsement of the 66/68 joint count for the measurement of musculoskeletal disease activity: OMERACT 2018 psoriatic arthritis workshop report - Duarte-García, A; Leung, Y; Coates, L; Beaton, D; Christensen, R; Craig, E; De Wit, M; Eder, L; Fallon, L; Fitzgerald, O; Gladman, D; Goel, N; et al. (Journal of Rheumatology, 2019)
Objective The Psoriatic Arthritis (PsA) Core Domain Set for randomized controlled trials and longitudinal observational studies has recently been updated. The joint counts are central to the measurement of the peripheral arthritis component of the musculoskeletal (MSK) disease activity domain. We report the Outcome Measures in Rheumatology (OMERACT) 2018 meeting’s approaches to seek endorsement of the 66/68 swollen and tender joint count (SJC66/TJC68) for inclusion in the PsA Core Outcome Measurement Set (COS). Methods Using the OMERACT Filter 2.1 Instrument Selection Process, the SJC66/TJC68 was assessed for (1) domain match, (2) feasibility, (3) numerical sense (construct validity), and (4) discrimination (test retest reliability, longitudinal construct validity, sensitivity in clinical trials, and thresholds of meaning). A protocol was designed to assess the measurement properties of the SJC66/TJC68 joint count. The results were summarized in a Summary of Measurement Properties table developed by OMERACT. OMERACT members discussed and voted on whether the strength of the evidence supported that the SJC66/TJC68 had passed the OMERACT Filter as an outcome measurement instrument for the PsA COS. Results OMERACT delegates endorsed the use of the SJC66/TJC68 for the measurement of the peripheral arthritis component of the MSK disease activity domain. Among patient research partners, 100% voted for a “green” endorsement, whereas among the group of other stakeholders, 88% voted for a “green” endorsement. Conclusion The SJC66/TJC68 is the first fully endorsed outcome measurement instrument using the OMERACT Filter 2.1 and the first instrument fully endorsed within the PsA COS.